The role of Rheum ribes roots alcoholic extract in reducing the effect of oxidative stress on the reproductive system of male rats - Abdalrahim H. Eefan; Saleh M. Rahim (Tikrit Journal of Pure Science, 2020)
The current study investigated the effect of Rheum ribes extracts alone or synergistically with zinc in the oxidative-antioxidatve status in semen of male rats exposed to oxidative stress with hydrogen peroxide (0.5%) and compared these effects with the role of vitamin E. 40 Male rats were used aged (12-14) weeks and weighed (130_220) g and randomly divided into (8) groups, 5 animals for each as follows: